WAYS OF IMPROVEMENT OF LOOP ENDARTERECTOMY RESULTS FROM ILIAC-FEMORAL SEGMENT - A. S. Ivanov; D. N. Maistrenko; M. I. Generalov; F. K. Zherebtsov; A. N. Oleshchuk; D. A. Granov; A. V. Gusinskiy; I. V. Mikhailov (Вестник хирургии имени И.И. Грекова)
The article presents an analysis of treatment results of 91 patients with iliac-femoral segment artery occlusion at the period from 2008 to 2014. Patients were divided into 2 groups: main group (n=30) consisted of patients who undergoing a half-closed loop endarterectomy with following implantation of stent-grafts in this area and control group (n=61) had patients whom were performed routine half-closed loop endarterectomy. The II degree of ischemia of lower extremities was in 88 (96,7%) patients and III degree had 3 (3,3%) patients. The areas of abnormalities of intravascular pattern were detected in 100% of cases in intraoperative angiography. They were modified using stent-grafts. A primary vascular patency was 100% in the first group and it numbered 65% in the second group during 5 years. The intraoperative angiography control with stent-graft implantation to the area of endarterectomy allowed reliable improvement of treatment results.